Vloga učitelja pri motivaciji učencev za učenje francoščine v Sloveniji - Premrl, Darja (Vestnik za tuje jezike, 2011)
French language teachers in Slovene elementary and high schools think that the teachers must motivate pupils with different approaches to work in the classroom. They also estimate that if the student isn't motivated to work in the classroom, teacher's effort could improve the motivation. Teachers, therefore, believe in their work, in their knowledge and competences to present French language to the pupils in the way they enjoy studying it, and that their way of work improves interest for the knowledge/learning of French language. Nevertheless, 78 % of teachers involved in this research think that a workshop about motivation with the examples from the good practice could be of great use to them. The analysis shows that teachers like to use student's book in their work and that they most often motivate pupils with their own excitement about the topic. The fact is that the motivation is a dynamic process which changes in time and in place. Teacher is a part of that process, but he/she is not the only one responsible for its outcome.
Keywords: motivacija; motivation; didactic method; didaktika; metodika; tuji jeziki; francoščina; French; učitelji; učenci; Slovenia; Slovenija